(untitled) (Construction Economics and Building, 2021)
Higher failure rates of construction business have been observed as a recurring phenomenon in the construction industry. This research focuses on the causes behind a range of performance modes of construction business. The growth and capacity under-investment archetype has been used as the main systems archetype to develop a causal structure for understanding the business performance. A system dynamics model was developed to create a simulation platform for the causal structure. A context of a typical small and medium construction company has been used in the simulation model. This research considered and experimented with a set of selected managerial policies and practices that can lead the construction business to failure, sustenance, or growth. In order to achieve the expected growth or sustenance, it is found that a certain level of balance needs to be secured on how much emphasis is to be given to win new projects, how much profit margins to work with, and how much capacities to be arranged and deployed for project operations, management, and execution.